Distorted Wave Theories Applied to Double Ionization by Ion Impact: Simulation of Higher-Order Processes. (17th May 2010) - Ciappina, M. F.; Kirchner, T.; Schulz, M.; Fischer, D.; Moshammer, R.; Ullrich, J.
Abstract : One of the goals in studies of double ionization (DI) of simple atoms by electron or ion impact is to elucidate and assess the different mechanisms that lead to this atomic process. In this work we present an attempt to model the mechanisms beyond the first order in DI of helium by highly charged projectiles. To this end we employ the continuum distorted wave-eikonal initial state (CDW-EIS) formalism joint with a Monte Carlo event generator (MCEG). The MCEG allows us to generate theoretical event files that represent the counterpart of the data obtained from a kinematically complete experiment. Starting from these event files, a new data analysis tool used to contrast theory and experiment in DI, the four-body Dalitz plots, is easily produced. The higher order mechanisms are simulated by considering DI as a sequential process: a single ionization of a helium atom as a first step and another single ionization of a single-charged helium ion as a second step. Some of the features in the experimental data are very well reproduced by these simulations.